Dimensi Konsep dan Praktis Barakah Sebagai Faktor Tersembunyi untuk Kelestarian Sosioekonomi Umat Islam - Abdullah, Atikullah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2014)
Achieving socio economic justice, equilibrium and sustainability has been the paramount objective of mankind since time immemorial. Towards that end, various philosophies, theories and approaches that based on different ideologies and ismes have been thought and presented. We can rest assured that there will be some more philosophies and approaches come into existence in the future. Yet the reality is that paramount objective seems to be even more illusive than ever. This paper argues that barakah is a hidden factor that has been unduly ignored in our quest for that objective. In doing that, this paper will refer to the present socio economic scenario and also benefitting from the signals and guidances from the Qur’an and the hadith together with the deliberation of the Islamic scholars relevant to the topic under dicsussion.